Religiusitas dan Kecemasan Mahasiswa Jurusan Psikologi Islam UIN Antasari dalam Menghadapi Pandemi Covid-19 - Yulianti, Sri Yuni; Mulyani, Mulyani; Hairina, Yulia (Islamic Psychology Study Program, Faculty of Ushluddin and Humanities, UIN Antasari Banj, 2021)
The Covid-19 pandemic, which has an increasing number of cases every day, and brings many changes in various aspects of life has resulted in many individuals who feel anxiety from the virus, including students. To overcome this anxiety by increasing worship, which in this case is related to religiosity. The research objective was to determine the level of religiosity and anxiety of UIN Antasari Islamic Psychology Department students in facing the Covid-19 pandemic, as well as the relationship between the two.This research uses quantitative research methods. The population was 565 students of the Islamic Psychology Department, while the sample was 113 students. The sampling technique is the random sampling technique. Research results: 1) There is no low-frequency religiosity level. Medium frequency 22 people (19.5%). High frequency 91 people (80.5%). 2) Low-frequency anxiety level does not exist. Medium frequency 74 people (65.5%). High frequency of 39 people (34.5%). 3) There is a significant relationship between religiosity and anxiety with a value of rxy = 0.208 and a significant level of p = 0.027 where (p <0.05) and together provide an effective contribution of 20%. And there is also a positive relationship in which the higher the level of religiosity, the higher the level of anxiety.